Giant Descending Thoracic Aortic Aneurysm: A Case Report - Zhumagaliyev, Rassul; Orazymbetov, Yerlan; Aitaliyev, Serik; Arslan, Sidar; Lenkutis, Tadas; Siudikas, Adakrius; Benetis, Rimantas (Acta medica Lituanica, 2025)
Background: Giant descending thoracic aortic aneurysm (GDTAA) is a rare vascular disease characterized by an aortic diameter exceeding 10 cm. GDTAA carries a significant risk of rupture and mortality and requires timely diagnosis and intervention. Despite the clinical severity of the disease, the literature on GDTAA remains sparse, particularly in cases with extreme aneurysmal dilatation.Case Presentation: We present the case of a 68-year-old man with a GDTAA of 14.08 × 10.04 cm, one of the largest ever reported. The patient initially presented with recurrent syncope, chronic cough and fatigue. Imaging studies, including Computed Tomography (CT) angiography, revealed a massive aneurysmal dilatation in the distal post-arch segment of the descending aorta with compression of the trachea and bronchi. The patient underwent a successful open surgical repair with a Dacron graft and simultaneous Coronary Artery Bypass Grafting (CABG). Postoperative complications included respiratory acidosis, emphysema and transient haemodynamic instability, which were effectively treated. The patient was discharged in a stable condition on the tenth postoperative day.Conclusion: This case highlights the importance of early recognition and surgical intervention in GDTAA in order to prevent catastrophic consequences. Comprehensive preoperative evaluation, careful surgical planning and attentive postoperative care are essential for optimal recovery. Our results emphasise the importance of modern imaging techniques for accurate anatomical assessment and risk stratification in patients with extreme aneurysm growth. Further research is needed to establish standardised protocols for the treatment of GDTAA.